2014
DOI: 10.1152/advan.00143.2013
|View full text |Cite
|
Sign up to set email alerts
|

Inspiring careers in STEM and healthcare fields through medical simulation embedded in high school science education

Abstract: The most effective ways to promote learning and inspire careers related to science, technology, engineering, and mathematics (STEM) remain elusive. To address this gap, we reviewed the literature and designed and implemented a high-fidelity, medical simulation-based Harvard Medical School MEDscience course, which was integrated into high school science classes through collaboration between medical school and K-12 faculty. The design was based largely on the literature on concepts and mechanisms of self-efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…This finding is support by Cerezo [42], who showed that PBLs were specifically effective for enhancing middle school girls' STEM self-efficacy. Dominguez and Jamie [48] also found that students were less likely to drop out of STEM courses if they engaged in PBL activities, while Berk and colleagues [78] showed that students who engaged in PBL had more positive attitudes toward STEM and were more interested in pursuing STEM-related careers. As such, PBL may be a critical learning experience in the pathway towards STEM majors and careers by increasing students' ability beliefs and intrinsic motivation for STEM subjects.…”
Section: Students' Beliefs About Ability Interest and Intrinsic Motimentioning
confidence: 98%
See 2 more Smart Citations
“…This finding is support by Cerezo [42], who showed that PBLs were specifically effective for enhancing middle school girls' STEM self-efficacy. Dominguez and Jamie [48] also found that students were less likely to drop out of STEM courses if they engaged in PBL activities, while Berk and colleagues [78] showed that students who engaged in PBL had more positive attitudes toward STEM and were more interested in pursuing STEM-related careers. As such, PBL may be a critical learning experience in the pathway towards STEM majors and careers by increasing students' ability beliefs and intrinsic motivation for STEM subjects.…”
Section: Students' Beliefs About Ability Interest and Intrinsic Motimentioning
confidence: 98%
“…Some studies have shown that students who engage in STEM PBLs have more positive attitudes toward and interest in pursuing STEM [41,44,78]. Several have found that engagement in PBL is associated with increased self-efficacy and confidence in STEM disciplines e.g., [41,42], which, in turn, could lead to more positive attitudes toward STEM and continued pursuit in STEM fields.…”
Section: Students' Beliefs About Ability Interest and Intrinsic Motimentioning
confidence: 99%
See 1 more Smart Citation
“…Career aspirations and self-efficacy (both general and subject-specific) have also been shown to be malleable in the short term as a consequence of student participation in specialized educational programs (Carpi et al, 2016;Berk et al, 2014). As such, we anticipated that participation in the Startup Tech program could plausibly affect students' career aspirations over the span of a school year, particularly for high school students on the verge of a transition to college or career.…”
Section: Student Self-efficacy and Career Aspirationsmentioning
confidence: 99%
“…Previous research indicated that it is possible for individual programs to increase students' reported self-efficacy and interest in specific STEM fields (Carpi et al, 2016;Berk et al, 2014), but the Startup Tech program might not be having these kinds of impacts on student mind-sets. The apparent lack of impact on student interest in computer science careers may stem from the fact that, in this administration of the course, students did not receive as much computer science instruction as was intended in the initial curriculum.…”
Section: Summary and Implicationsmentioning
confidence: 99%